Provincial Overdose Cohort: Population Data Linkage During an Overdose Crisis - Xavier, Chloé; Zhao, Bin; Gan, Wen Qi; Slaunwhite, Amanda (International Journal of Population Data Science, 2020)
Introduction In 2016, the Provincial Overdose Cohort (ODC) was created following the declaration of the public health emergency in British Columbia (BC), Canada. The ODC is a set of longitudinal and linked administrative data which identifies illicit drug-related overdose events, including death, ambulance, emergency room, hospital, physician, and prescription drug records. Objectives and Approach The ODC was developed to better understand factors associated with overdose in order to support response activities, prevent overdose deaths, and identify trends and opportunities for interventions. Person-level linkages were conducted using provincial health insurance and health history data; socio-economic information, mental and physical illness diagnoses, and corrections history were also appended. The ODC currently includes people who have had a drug-related overdose between January 1 st 2015 and December 31 st 2017 as well as a 20% random sample of the general population. Results The ODC contains 36,576 overdose episodes and 23,161 people who have a drug-related overdose between January 1 st , 2015 and December 31 st 2017. Of the 23,161 people, 3,604 (15.6%) had a fatal overdose and 19,557 (84.4%) had a non-fatal overdose. 49.9% of people in BC who had an overdose were 20-39 years of age and 67.4% were males. From 2015 to 2017, the proportion of people experiencing 3 or more overdoses a year increased from 3.6% to 8.7%, respectively. There were an increasing number of fatal and non-fatal drug-related overdoses in BC during this time period. Conclusion / Implications Large population data linkages can be invaluable tools during a public health emergency. Collaborative partnerships and a shared data governance across jurisdictions was central in building the ODC and understanding how various social determinants of health impact risk of overdose among people who use drugs.